Current Achievement and Future Plan for Improvement for E Cutter Development - Abdul Shukor, Fairul Azhar; Misron, Norhisam; Wakiwaka, Hiroyuki; Tashiro, Kunihisa; Nirei, Masami (2012)
E Cutter is a harvesting tool dedicated for oil palm fresh fruit bunch (FFB). It employed rapid chopping method and bunch harvest as it harvesting method. The E Cutter development was inspired by the usage of CantasTM which currently efficient tool for oil palm FFB harvesting. However, due to height limitation that influences the operation of CantasTM, the development of E Cutter was seen as a breakthrough to at least maintaining the performance of CantasTM in harvesting higher palm tree. Both of E Cutter and CantasTM comprise three major parts. There are energy provider part at the bottom, actuator part at the top and energy transmitter in the middle. Compared to CantasTM that totally applies mechanical system, the E Cutter is applies the electrical system especially in the actuator and energy transmitter part. However, in this paper, the progress of the E Cutter actuator development was focused. The previous achievement of the actuator and future planning for improvement will be explained. In the end part of this paper, the design target and type of future actuator will be developed for E Cutter also has been stated.